Risk of Esophageal Cancer Following Percutaneous Endoscopic Gastrostomy in Head and Neck Cancer Patients: A Nationwide Population-Based Cohort Study in Taiwan. Issue 9 (March 2016) - Lin, Kuen-Tze; Lin, Chun-Shu; Lee, Shih-Yu; Huang, Wen-Yen; Chang, Wei-Kuo
Abstract : Abstract: Esophageal cancers account for majority of synchronous or metachronous head and neck cancers. This study examined the risk of esophageal cancer following percutaneous endoscopic gastrostomy (PEG) in head and neck cancer patients using the Taiwan National Health Insurance Research Database. From 1997 to 2010, we identified and analyzed 1851 PEG patients and 3702 sex-, age-, and index date-matched controls. After adjusting for esophagitis, esophagus stricture, esophageal reflux, and primary sites, the PEG cohort had a higher adjusted hazard ratio (2.31, 95% confidence interval [CI] = 1.09–4.09) of developing esophageal cancer than the controls. Primary tumors in the oropharynx, hypopharynx, and larynx were associated with higher incidence of esophageal cancer. The adjusted hazard ratios were 1.49 (95% CI = 1.01–1.88), 3.99 (95% CI = 2.76–4.98), and 1.98 (95% CI = 1.11–2.76), respectively. Head and neck cancer patients treated with PEG were associated with a higher risk of developing esophageal cancer, which could be fixed by surgically placed tubes.